The value of long‐term in situ soil moisture and snowpack monitoring: Laying the foundation for future studies in the Upper Missouri River Basin - Mingxiu Wang; Briana M. Wyatt (Vadose Zone Journal)
Abstract In recent decades, the Upper Missouri River Basin (UMRB) has experienced record floods (2011 and 2019) and severe flash droughts (2012 and 2017). These natural disasters are closely associated with soil moisture and snowpack conditions, and are expected to increase in frequency in the future due to climate change. Long‐term monitoring data not only provide ground‐truth soil moisture and snow cover information useful for the prediction of the aforementioned natural disasters, but also have applications in water resources management, such as streamflow forecasting and irrigation scheduling. However, the present insufficient spatial coverage of monitoring stations within the UMRB restricts development of such applications and has led to a subsequent ongoing expansion of monitoring within the UMRB as part of the U.S. Army Corps of Engineers UMRB Monitoring Network. In this review, we summarize the existing in situ monitoring data sources in the UMRB, review prior applications of long‐term soil moisture and snowpack monitoring data to support public objectives such as drought and flood early warning, and suggest challenges and recommendations for future research. As a part of the National Oceanic and Atmospheric Administration National Integrated Drought Information System UMRB Soil Moisture and Snowpack Data Value Study, this review emphasizes the high potential value of such soil moisture and plains (i.e., below 5500 feet) snowpack monitoring data both within the UMRB and beyond.